2011
DOI: 10.1021/ja204910n
|View full text |Cite
|
Sign up to set email alerts
|

Amplification, Mutation, and Sequencing of a Six-Letter Synthetic Genetic System

Abstract: The next goals in the development of a synthetic biology that use artificial genetic systems will require chemistry-biology combinations that allow the amplification of DNA containing any number of sequential and non-sequential non-standard nucleotides. This amplification must ensure that the non-standard nucleotides are not unidirectionally lost during PCR amplification (unidirectional loss would cause the artificial system to revert to an all-natural genetic system). Further, technology is needed to sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
205
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(213 citation statements)
references
References 30 publications
(46 reference statements)
2
205
0
2
Order By: Relevance
“…9) Recently, they applied the six-letter genetic system with the P : Z pair to the cell-systematic evolution of ligands by exponential enrichment (SELEX) system and succeeded in obtaining highly active aptamers against HepG2 liver cancer cells. and 2,4-difluorotoluene (F) as steric isosteres of the natural A : T pair 12,13) (Fig.…”
Section: Medicinal and Bioorganic Chemistry Of Nucleosides And Nucleomentioning
confidence: 99%
See 1 more Smart Citation
“…9) Recently, they applied the six-letter genetic system with the P : Z pair to the cell-systematic evolution of ligands by exponential enrichment (SELEX) system and succeeded in obtaining highly active aptamers against HepG2 liver cancer cells. and 2,4-difluorotoluene (F) as steric isosteres of the natural A : T pair 12,13) (Fig.…”
Section: Medicinal and Bioorganic Chemistry Of Nucleosides And Nucleomentioning
confidence: 99%
“…7d). Although the replication fidelity of the ImN N : NaO O pair is slightly inferior to those of other unnatural base-pair analogs, 8,9,26,28,34,46,47) it is strongly indicated that the ImN N : NaO O pair acts as an orthogonal base pair for WC base pairs during PCR amplification.…”
Section: Investigation Of Single Nucleotide Insertion With the Imnmentioning
confidence: 99%
“…In this context, the dZ:dP pair consisting of two non-standard nucleoside analogues (dZ 7 and dP 8, Figure 2) with a different hydrogen bond pattern, has advanced as a potent surrogate of a natural base pair and is thus a potential candidate for a six-letter (ACGTZP) synthetic genetic system 40 . While polymerases such as…”
Section: Figurementioning
confidence: 99%
“…In 2011, Hirao's team reported that DNA containing an unnatural hydrophobic base pair, called Ds and Diol1-Px, could be copied with 99.77-99.92% fidelity per replication 9 . The same year, Benner and his colleagues showed that another unnatural base pair -P and Z, which join using hydrogen bonds -achieved fidelity of 99.8% per replication 10 . And in July, Romesberg's team reported rates of 99.66-99.99% for optimized versions of his bases, called NaM and 5SICS (ref.…”
Section: Base Jumpingmentioning
confidence: 99%
“…Researchers haven't shown that polymerases can copy more than four of the paired bases in a row 10 . The polymerase is "the hard nut to crack", says Benner.…”
Section: Base Jumpingmentioning
confidence: 99%